Răspunsuri

  • Utilizator Brainly
2014-02-15T09:58:11+02:00
(1/3)^2=1/9
(0,25-1/6)-1/3=(1/4-1/6)-1/3=(3/12-2/12)-1/3=1/12-1/3=1/12-4/12=-3/12=-1/4
(1/3)^2 : (0,25 - 1/6) - 1/3 =
= 1/9 : (1/4 - 1/6) -1/3 =
= 1/9 : (3/12 - 2/12) - 1/3 =
= 1/9 : 1/12 - 1/3 =
= 1/9 * 12/1 - 1/3 =
= 4/3 - 1/3 =
= 2/3 .
scuze nu am fost atent si la impartire
2014-02-15T12:31:43+02:00
(1/3)^2 : (0,25 - 1/6) - 1/3 = 
= 1/9 : (1/4 - 1/6) -1/3 =
= 1/9 : (3/12 - 2/12) - 1/3 =
= 1/9 : 1/12 - 1/3 =
= 1/9 * 12/1 - 1/3 =
= 4/3 - 1/3 =
= 2/3 .